2022
DOI: 10.1002/jmv.27677
|View full text |Cite
|
Sign up to set email alerts
|

Association of viral load with age, gender, disease severity, and death in severe acute respiratory syndrome coronavirus 2 variants

Abstract: In this study, the relationship between viral load, demographic characteristics, and disease information in 1007 (48.5%) patients with Delta variant (B.1.617.2), and 1070 (51.5%) patients with Alpha variant (B1.1.7) were investigated. We found that there was a significant difference in viral load between patients who died from the Alpha variant and those who were discharged (p < 0.05). Nevertheless, no significant difference was observed in patients with the Delta variant. The viral load in patients who died f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 30 publications
(61 reference statements)
1
6
0
Order By: Relevance
“…Our study shows that the Delta variant spread more in the younger age groups than the Alpha variant similar to other studies [1,37,38]. According to the determination of the Delta variant which was mostly detected in younger patients in our study was the dominant mu-…”
Section: Discussionsupporting
confidence: 91%
“…Our study shows that the Delta variant spread more in the younger age groups than the Alpha variant similar to other studies [1,37,38]. According to the determination of the Delta variant which was mostly detected in younger patients in our study was the dominant mu-…”
Section: Discussionsupporting
confidence: 91%
“…For example, a study conducted in the USA reported a significantly higher viral load in males 26 , and the same trend was observed in Italy, although it was found that males had a faster viral load decay than females, and the viral load decayed more slowly in older patients 27 . Studies from Australia 28 and Turkey 29 , on the other hand, reported no significant difference in viral loads among patients of different sexes and age groups. This suggests that the trends may vary from setting to setting, and the association between viral load dynamics and age or sex remains highly debated.…”
Section: Discussionmentioning
confidence: 91%
“…However, the viral trajectory such as mean peak Ct value, mean proliferative stage duration, clearance stage duration and days from peak between them was different, and the Ct peak in SARS-CoV-2 infection was earlier than SARS-CoV and MERS-CoV [6]. Also, various factors such as individual characters; age, sex, underlying disease, and obesity [3,[7][8][9], virus types of SARS-CoV-2 [10][11][12][13][14][15][16][17][18], treatment, and vaccination history of infectors affected the curve from beginning to end in periods of SARS-CoV-2 infection [19][20][21][22]. So, it is not clear exactly when the viral shedding peak is and how much the difference in viral load at the peak in SARS-CoV-2 virus infection.…”
Section: Many Studies Have Shown That Like Other Respiratory Viruses ...mentioning
confidence: 99%
“…However, the viral trajectories differ among factors such as mean peak Ct value, mean proliferative stage duration, clearance stage duration, and days from peak, and the Ct value peaks earlier in SARS-CoV-2 infections than for the 2003 severe acute respiratory syndrome or MERS-CoV [ 6 ]. Furthermore, factors such as individual characteristics (age, sex, underlying disease, and obesity) [ 3 , 7 - 9 ], variant types of SARS-CoV-2 [ 10 - 18 ], treatment, and vaccination history have affected the curve from beginning to end in periods of SARS-CoV-2 infection [ 19 - 22 ]. Thus, it is not clear exactly when viral shedding peaks and how much difference there may be in the viral load at the peak of a SARS-CoV-2 infection.…”
Section: Introductionmentioning
confidence: 99%